Discontinuity formulation of restitutions in Aceh qanun against the protection of rape victims - Rahmatillah Aljamalulail, Syarifah (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2021)
This study discusses the fulfilment of the rights of rape victims in Aceh in the form of restitution payments. Restitution which is the main punishment in Qanun Aceh No. 6 of 2014 concerning the Jinayat Law, has never been included in the judge's decision in the cases of rape. Basically Qanun Jinayah has shown its side with rape victims by formulating punishments for perpetrators which are certain to have a deterrent effect such as the length of prison sentences and the number of sentences handed down to the perpetrators. However, the problem of hampering the fulfilment of restitution to victims is a new problem in the realm of enforcing the Jinayah Qanun in Aceh. This raises the question of why restitution was never included in the decision of the Sharia Court for the rape case in Aceh. This research is a literature study using a normative approach which is then explained descriptively. The results of this study showed that the restitution was never included in the decision is due to the incompatibility of the restitution formulation mentioned in the Jinayat Law Qanun and later referred to differently in the Jinayat Procedural Law, namely as compensation. The fulfilment of this right to restitution is also hampered due to the absence of a governor's regulation that contains technical rules regarding the mechanism for executing restitution for victims. The impact of this discontinuity in the formulation of restitution makes judges unable to include sanctions for restitution in their decisions.